The disease burden of migraine patients receiving prophylactic treatments in Korea: a population-based claims database analysis - Seonyoung Park; Sola Han; Hae Sun Suh (BMC, 2022)
Abstract Background Despite guideline recommendations, the limited benefits and failure of prophylactic treatment in patients with migraine have been reported. This study aimed to estimate the incremental burden (i.e., healthcare resource use and cost) of disease in patients who received at least one prophylactic treatment compared to those who did not. Methods This study analyzed the Health Insurance Review and Assessment Service database, which covers the entire population of Korea from December 2014 to November 2019. We included adult patients with migraine (≥18 years) who had ≥1 claim with migraine diagnosis (G43) or received ≥1 prescription of triptan or ergotamine between December 2015 and November 2018. We defined two groups: (1) migraine patients who received at least one prophylactic treatment (prophylaxis group) and (2) migraine patients who never received prophylactic treatments (non-prophylaxis group). We performed propensity score matching to balance the baseline covariates between the two groups. In a matched cohort, we estimated healthcare resource use and costs in terms of outpatient visits, outpatient visits to neurologists, emergency department (ED) visits, and hospitalizations. Results After matching, 633,709 and 633,709 patients were identified in the prophylaxis and non-prophylaxis groups, respectively. The healthcare resource utilization was significantly higher in the prophylaxis group than in the non-prophylaxis group in terms of the number of outpatient visits (2.34 vs 1.70), outpatient visits to neurologists (2.23 vs 1.61), ED visits (1.07 vs 1.05), and hospitalizations (1.12 vs 1.09) (all P <  0.05). The estimated annual costs per patient were significantly higher in the prophylaxis group than in the non-prophylaxis group for outpatient (102.37 USD vs. 62.46 USD), neurology outpatient (141.80 USD vs. 120.30 USD), and ED visits (550.51 USD vs. 234.14 USD) and hospitalization (817.01 USD vs. 645.97 USD) (all P <  0.001). Conclusions Migraine patients who received ≥1 prophylactic treatment had a higher burden of disease than migraine patients who received no prophylaxis. This indicates that despite migraine prophylaxis, the migraine-related disease burden remains high, and more efficient migraine prophylaxis strategies are needed.